DUNIA PERFILMAN INDONESIA: REPRESENTASI TOXIC MASCULINITY PADA FILM NGERI-NGERI SEDAP - Basuki, Luthfi Nugraha; Nabila Nabila; Sevty Adinia; Aghnia Dian Lestari (CV. AFDIFAL MAJU BERKAH, 2024)
This study explores the representation of toxic masculinity in the film ”Ngeri-Ngeri Sedap”, as exemplified by the character Mr. Domu, the patriarch of a Batak family. His behavior mirrors the patriarchal structure embedded within his family dynamics. The research employs a qualitative approach, utilizing John Fiske’s semiotic analysis, which is structured into three levels: the Level of Reality (focusing on behavior and expression), the Level of Representation (analyzing camera shots and lighting), and the Level of Ideology (uncovering underlying ideological messages). Data was gathered through observation, interviews, and documentation. Through semiotic analysis, the study reveals both verbal and non-verbal signs, such as the characters' behaviors, expressions, and dialogues within the film. Toxic masculinity in Mr. Domu manifests in various ways, including his stubbornness, insistence on appearing strong, authoritarian attitude, refusal to be contradicted, and obsession with achieving high social status to earn respect. He also enforces emotional suppression, such as prohibiting expressions of sadness or crying, especially in front of his family. These behaviors are indicative of the harmful aspects of masculinity that are often misinterpreted, misused, and imposed upon others. Moreover, the film highlights an ideology of individualism, which tends to disregard the needs and desires of others.